Identificação de fontes de sedimento em bacias hidrográficas rurais do sul do Brasil - Tiecher, Tales (2015)
Knowledge of the main diffuse sources of sediment can enhance efficiency in the use of public resources invested in soil conservation management strategies. Conventional fingerprinting methods based on geochemical composition are time-consuming and require critical preliminary sample preparation. In this context, spectroscopic methods can be less labor-intensive, cheap, and viable alternative for this purpose. The present study aimed to quantify the sediment sources supplied to rivers in agricultural catchments of Rio Grande do Sul State, Brazil, and to evaluate the potential use of spectroscopy measurements as a low cost and easy alternative to fingerprint sediment sources. Five study areas with increased size (Arvorezinha, Júlio de Castilhos 1, Júlio de Castilhos 2, Conceição, and Guaporé, with areas of 1.19, 0.80, 1.43, 804.3, and 2,027.2 km2, respectively) were evaluated. Sediment sources evaluated were crop fields, grasslands, unpaved roads, and stream channels. Sediment sampling strategies included time-integrated samplers, fine-bed sediments, and storm-event sediments. The total concentrations of several geochemical tracers were measured in both sediment and source samples. Spectral measurements were made for ultraviolet-visible, near-infrared, and mid-infrared ranges only for the Arvorezinha catchment. Source ascriptions obtained by alternative methods based on spectroscopy analysis were in agreement with ascriptions from classical fingerprinting method based on geochemical composition. Spectral information can provide as relevant information as the geochemical tracers. Furthermore, combining visible-based-colour with geochemical tracers was a rapid and cheap way to enhance discrimination between source types and to improve the precision of sediment sources apportionment. Results of sediment source apportionment demonstrate that other factors than proportion of land use, such as distribution of croplands, forests, and unpaved roads across the landscape play an important role in sediment production. Riparian forests seems to be a key factor to control stream channel erosion. The sediment yielded from unpaved roads seems to be strongly scale-related and it depends on the number of intersections between roads the stream network. Crop fields, even when cultivated with no-tillage, are still the main source of sediment to rivers in agricultural catchments in Southern Brazil. The amount of cropland specific sediment yield ranged from 0.06 to 3.95 ton ha-¹ yr-¹. These variations are partly attributed to the relief and slope, but land use and soil management are also important control factors. The cropland specific sediment yield remains too high for areas with low sensitivity to erosion where no-tillage is applied, as in Conceição catchment (1.30 ton ha -¹ of cropland yr-¹), indicating that additional efforts are necessary to further reduce soil erosion. Therefore, there is an urgent need to better plan land use and cover in these catchments, inasmuch as the soil management systems used by farmers proved to be inefficient to reduce runoff and erosion in cultivated areas of Southern Brazil.